International Business - Simon Collinson; Rajneesh Narula; Amir Qamar; Alan M Rugman (Hoboken, NJ Pearson, 2020)
This textbook connects tried-and-tested theory, analytical frameworks, data and case examples to deliver a comprehensive guide to the subject from authors who keep pace with the ongoing developments in both theory and practice.
Keywords: International business enterprises; Management; International Business and Management (ECO2023-N ); (BIN3022-N) Global Economics & Business Operations